Effect of H Defects on Li Transport during the Deposition Process on an H‐Diamond Surface: A First‐Principles Calculation Analysis. Issue 8 (18th June 2020) - Ren, Yuan; Ma, Xiyu; Qi, Zhaohui; Yang, Shenbo; Zhang, Chao; Sun, Shiyang; Cao, Yanan; Tan, Xin; Liu, Xuejie
Abstract: To explore the feasibility and rationality of a hydrogen‐terminated diamond surface film as an solid electrolyte interface (SEI) for lithium‐sulfur batteries, the adsorption and migration behavior of lithium atoms on the hydrogen‐terminated diamond surface with different amounts of hydrogen defects are determined by first‐principles calculations. Since a hydrogen deficiency in the row direction is denser than a hydrogen deficiency in the chain direction, hydrogen deficiency can drive lithium‐ion deposition. Thus, lithium atoms are more stable on the surface of hydrogen‐terminated diamonds with a hydrogen deficiency in the direction of the dimer row. The adsorption of lithium atoms on hydrogen‐terminated diamond films lacking three hydrogens is more stable due to the absence of dangling chemical bonds on the surface of the hydrogen‐terminated diamond. Therefore, lithium atoms cannot be adsorbed on an all‐H‐diamond surface. The low adsorption energy of lithium atoms on a clean diamond surface indicates that it is a simple physical adsorption. H termination increases the adsorption energy and migration activation energy of Li on the diamond surface. H termination changes the migration path of Li on the diamond surface. The atomic deposition of Li is driven by the center of the H defect region on the H‐diamond surface. Abstract : H termination increases the adsorption energy, migration activation energy, and the migration path of Li on a diamond (001) surface. The atomic deposition of Li is driven by the center of the H defect region on the H‐diamond (001) surface.